Initial experience of coiling cerebral aneurysms using the new Comaneci device. (2nd July 2015) - Lawson, Aimee Louise Deborah; Chandran, Arun; Puthuran, Mani; Goddard, Tony; Nahser, Hans; Patankar, Tufail
Abstract : We present our initial patient experience with an innovative temporary bridging device, the Comaneci (Rapid Medical, Israel), to assist in the coiling of cerebral aneurysms. The Comaneci device confers the same benefits as balloon remodeling but without the risks of parent artery occlusion. This alleviates time pressure on the clinician, and could reduce the risk of parent artery thrombosis. Three patients were treated with the Comaneci device. Two patients had acute ruptured posterior communicating aneurysms and one patient was treated electively for a carotico-ophthalmic aneurysm. Excellent occlusion of all three aneurysms was obtained. One patient developed a distal middle cerebral artery clot, that was treated with intravenous aspirin, with minor neurological consequences. These early results show that the Comaneci device can be used to achieve good cerebral aneurysm occlusion. Vessel patency is maintained throughout the procedure with potential advantages over conventional balloon assisted coiling.